ANALISIS DAMPAK PEMECAHAN SAHAM (STOCK SPLIT) TERHADAP TRADING VOLUME ACTIVITY dan ABNORMAL RETURN PADA SAHAM YANG TERDAFTAR DI BEI TAHUN 2011-2015 - Situmorang, Benhard Partogi; Mahfud, Mohammad Kholiq (Faculty of Economics and Business Diponegoro University, 2016)
There are some variety of corporate action policy that corporate is able to influence the number of outstanding shares, and share’s value to attract the investor. One of the corporate action is stock split. Stock split is splitting shares amount by splitting the shares volume to generate the cheaper price of shares and increase the share volume. This research conducted to verify the relationship between stock split and abnormal return of share using market adjusted model and trading volume activity using the wilcoxon rank signed test on the event window which is 5 day before and 5 day after the stock split announcement day. This research use the event study with the Independent Sample t-test and normality tes as the method. The research shows that the stock split announcement doesn’t give difference significantly for the abnormal return, however the effect of stock split is significantly negative to trading volume activity. There are some alteration in the amount of abnormal return, but the amount is not significant. On the other hand, the trading volume activity show the significant changes. The amount slightly go down into negative side after the stock split.